H19 lncRNA alters stromal cell growth via IGF signaling in the endometrium of women with endometriosis. Issue 8 (18th June 2015) - Ghazal, Sanaz; McKinnon, Brett; Zhou, Jichun; Mueller, Martin; Men, Yi; Yang, Lihua; Mueller, Michael; Flannery, Clare; Huang, Yingqun; Taylor, Hugh S
Abstract Endometriosis affects approximately 15% of reproductive aged women and is associated with chronic pelvic pain and infertility. However, the molecular mechanisms by which endometriosis impacts fertility are poorly understood. The developmentally regulated, imprinted H19 long noncoding RNA (lncRNA) functions to reduce the bioavailability of microRNA let‐7 by acting as a molecular sponge. Here we report that H19 expression is significantly decreased in the eutopic endometrium of women with endometriosis as compared to normal controls. We show that decreased H19 increases let‐7 activity, which in turn inhibits Igf1r expression at the post‐transcriptional level, thereby contributing to reduced proliferation of endometrial stromal cells. We propose that perturbation of this newly identified H19/Let‐7/IGF1R regulatory pathway may contribute to impaired endometrial preparation and receptivity for pregnancy in women with endometriosis. Our finding represents the first example of a lncRNA‐based mechanism in endometriosis and its associated infertility, thus holding potential in the development of novel therapeutics for women with endometriosis and infertility.